INFLUENCE OF MOTIVATION AND PERFORMANCE WORK THE PERFORMANCE OF EMPLOYEES IN TRAIN INDONESIA COMPANY TANJUNG KARANG BANDAR LAMPUNG (A CASE STUDY IN THE COMMERCIAL EMPLOYEES) - Endang Siswati Prihastuti; Elvira Sisilia (International Conference On Law, Business and Governance (ICon-LBG), 2016)
PT Kereta Api Indonesia (Persero)Tanjung Karang, Bandar Lampung is a company engaged in the field of passenger and freight services to and from Lampung - South Sumatra. In conducting its business PT.KAI faces a sales realization of passenger transport services have not reached the target with an average of 82.38 % of the expected target. The problems in this study is whether the motivation to work a significant effect on the performance of employees, whether working ability significantly influence employee performance, and whether the motivation and ability to work together have a significant effect on the performance of the Commercial Section employees at PT. KeretaApi Indonesia (Persero) Tanjung Karang Bandar Lampung. This study aims to determine the effect of work motivation on employee performanceto determine the effect on the performance of employees working ability, and to determine the influence of motivation and ability to work together on employee performance Commercial Section at PT.Kereta Api Indonesia (Persero) Tanjung Karang, Bandar Lampung. The hypothesis proposed is: work motivation significantly influence employee performance, workability significant effect on employee performance and motivation and ability to work together have a significant effect on the performance of the Commercial Section employees at PT. KeretaApi Indonesia (Persero) Tanjung Karang, Bandar Lampung.This research used descriptive research that explains the causal relationship between the variables through hypothesis testing. Respondents in this study all members of a population of 27 employees of the Commercial Section at PT.KeretaApi Indonesia (Persero) TanjungKarang, Bandar Lampung. Data collection techniques used in this study is the observation, documentation, interviews and questionnaires . The analytical method used is to use the analysis of qualitative and quantitative data. Qualitative analysis is the interpretation of the data obtained in the study, while the quantitative analysis includes: validity and reliability, multiple regression analysis, coefficient of determination, hypothesis testing through t test and F.From the discussion, work motivation, ability to work, the employee's performance in the Commercial Section PT. KeretaApi Indonesia (Persero) Tanjung Karang Bandar Lampung is at a level good enough. The results of multiple regression analysis states that motivation and ability to work both partially and simultaneously have a significant influence on employee performance. From the test of determination ( R2 ) can be determined that the motivation and ability of work obtained yield was 0.823 , which means the employee's performance is affected by factors of motivation and work ability by 82 % , while the remaining 18% of the employee's performance is influenced by other variables not examined in the study this. So that the hypothesis can be accepted.